2012
DOI: 10.1158/0008-5472.can-11-2651
|View full text |Cite
|
Sign up to set email alerts
|

Type I and II IFNs Inhibit Merkel Cell Carcinoma via Modulation of the Merkel Cell Polyomavirus T Antigens

Abstract: Merkel cell carcinoma (MCC) is a rare and highly aggressive skin cancer associated with the Merkel cell polyomavirus (MCV). As MCC cell lines show oncogene addiction to the MCV T antigens, pharmacologic interference of the large T antigen (LTA) may represent an effective therapeutic approach for this deadly cancer. In this study, we investigated the effects of IFNs on MCC cell lines, especially on MCV-positive (MCV þ ) lines. Type I IFNs (i.e., Multiferon, a mix of different IFN-a subtypes, and IFN-b) strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 48 publications
1
46
0
Order By: Relevance
“…Importantly, treatment of MCC cell lines with type-I interferons, etoposide (a standard MCC chemotherapeutic) and radiation, can all induce MHC-I upregulation in vitro [52]. Notably, in vitro treatment of MCC cells lines with type-I interferons also reduced expression of MCPyV LT, which may further promote tumor destruction [53]. Downregulation of MHC-I can also be reversed in vivo and will be discussed subsequently in the context of intralesional IFN treatment.…”
Section: Mhc-i Downregulationmentioning
confidence: 99%
“…Importantly, treatment of MCC cell lines with type-I interferons, etoposide (a standard MCC chemotherapeutic) and radiation, can all induce MHC-I upregulation in vitro [52]. Notably, in vitro treatment of MCC cells lines with type-I interferons also reduced expression of MCPyV LT, which may further promote tumor destruction [53]. Downregulation of MHC-I can also be reversed in vivo and will be discussed subsequently in the context of intralesional IFN treatment.…”
Section: Mhc-i Downregulationmentioning
confidence: 99%
“…Epidemiologic and experimental evidence both strongly suggest that mcc is controlled by the immune system [18][19][20][21][22] . Advanced age and immunosuppression favour the development of mcc and are suggested to be responsible for a strong rise in the incidence of mcc since the mid-1980s 18 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, type I IFN is able to induce apoptosis in MCPyV + MCC cell lines in vitro and in vivo through the modulation of the virally encoded LTA: IFN type I reduces the expression of the MCV LT and increases the expression of promyelocytic leukemia (PML) protein, which interferes with the function of the LT (30). Furthermore, a multicenter study revealed that isolated hyperthermic limb perfusion with tumor necrosis factor-α, IFN-γ, and melphalan resulted in a complete or partial response of locally advanced MCC (31).…”
Section: Immunotherapymentioning
confidence: 99%